Peculiarities of marketing policy implementation in a banking institution - Ya.A. (Економіка, управління та адміністрування)
The article discusses the foundations of marketing policy, its components, and the specifics of its formation in a banking institution. The article highlights the gaps in the scientific research regarding the analysis of marketing policy, including a lack of generalized interpretation of the concept and often-individual interpretations without considering the concept in general. It emphasizes the importance of studying marketing policy due to its significance in business. The article provides a terminological analysis of the concept of marketing policy, concluding that it covers not only the organization of marketing activities but also reflects the culture and values of an economic entity. The author offers a personalized interpretation of the concept of marketing policy. The article also considers the features of marketing policy in a banking institution, identifying its main differences. Additionally, it highlights the components of the marketing policy of an economic entity, including commodity policy, pricing policy, sales policy, communication policy, marketing research, and innovative marketing. Finally, the article presents a comparative analysis of the formation of the components of the marketing policy of an enterprise and bank, highlighting their main differences. An interpretation of a banking institution's marketing policies has been proposed.